Innovation in Meeting the Needs of Indigenous Inmates in Australia. - Grant, Elizabeth (Corrections Today)
The article discusses the innovations at the facilities of the Kimberley Prison in Western Australia to meet the cultural and environmental needs of indigenous inmates. The Western Australian government's move is geared to reduce overrepresentation and reoffending of indigenous inmates on prisons and corrections through a community consultation model. The new facilities cater to the indigenous inmates' cultural needs, family and community responsibilities, and spiritual connections.